2003
DOI: 10.2514/2.6099
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Model for the Impulse of Single-Cycle Pulse Detonation Tube

Abstract: An analytical model for the impulse of a single-cycle pulse detonation tube has been developed and validated against experimental data. The model is based on the pressure history at the thrust surface of the detonation tube. The pressure history is modeled by a constant pressure portion, followed by a decay due to gas expansion out of the tube. The duration and amplitude of the constant pressure portion is determined by analyzing the gasdynamics of the self-similar ow behind a steadily moving detonation wave w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(107 citation statements)
references
References 21 publications
6
101
0
Order By: Relevance
“…However, we would point out that the analytical results are based on a simplified method, while the experimental results are also subject to error bars due to measurement and other uncertainties, and the predicted detonation speed is supported by published higher fidelity CFD results [49]. For acetylene, also, our predicted detonation velocity matches exactly a separate published experimental measurement [47] and agrees within 6% with the same analytical analysis [48], such that our model predictions fall within the bounds of these few other available published findings. We believe this suggests that our adopted methodology is an appropriate one, at least for such an initial investigation of biofuel alternatives, which are all predicted to have a very closely similar (3% variation) higher detonation velocity.…”
Section: Validation Of the Modelsupporting
confidence: 79%
See 1 more Smart Citation
“…However, we would point out that the analytical results are based on a simplified method, while the experimental results are also subject to error bars due to measurement and other uncertainties, and the predicted detonation speed is supported by published higher fidelity CFD results [49]. For acetylene, also, our predicted detonation velocity matches exactly a separate published experimental measurement [47] and agrees within 6% with the same analytical analysis [48], such that our model predictions fall within the bounds of these few other available published findings. We believe this suggests that our adopted methodology is an appropriate one, at least for such an initial investigation of biofuel alternatives, which are all predicted to have a very closely similar (3% variation) higher detonation velocity.…”
Section: Validation Of the Modelsupporting
confidence: 79%
“…Only the results for acetylene and kerosene fuels could be validated in this way. Model results for acetylene fuel were compared with the experimental data of Turns [47] and an analytical study by Wintenberger [48], while comparisons for kerosene fuel were made with the analytical study of Wintenberger [48] and the time-dependent Computational Fluid Dynamics (CFD) of Yungster [49], as well as experimental work conducted by Cheatham [50] for a range of fuel droplet sizes. The detonation velocity is taken at the von Neumann spike, while pressure rise is taken as time-averaged.…”
Section: Validation Of the Modelmentioning
confidence: 99%
“…This value is reported as a different value. For example, Zitoun et al, 15) Wintenberger et al, 16) and Kailasanath 1) proposed K ¼ 5:3, 4.8 and 4.65, respectively. Though the above researchers proposed K as an empirical value, Endo et al 17) proposed an approximate solution without empirical parameters.…”
Section: Single-shot Thrust Performance For Simplified Pdesmentioning
confidence: 99%
“…Many researchers 1,[15][16][17][18] have reported that the thrust of a simplified PDE with a straight tube with a filling fraction of 1.0 is predicted by the following Eq. (1):…”
Section: Single-shot Thrust Performance For Simplified Pdesmentioning
confidence: 99%
“…The time of arrival of the first characteristic of the reflected expansion head (and the boundary of the simple region) can be obtained via a similarity solution [24]. This solution accounts for the interaction of the reflected head with the incident wave (see Fig.…”
Section: Reservoir Depletion Time Scalesmentioning
confidence: 99%